Estabilidad angular de un sistema eléctrico de potencia considerando la integración de regulaciones de velocidad y voltaje. - Antamba Ávila, Daniela Anabel (2018)
Angle stability has a highly importance in Power Systems as their study and comprehension allows to maintain in normal conditions of working "synchronism" to the machines of the system after being affected by a disturbance. In this paper is presented a development that allows to observe the behavior of a power system undergone a disturbance in transient period of time, including the generators, speed and voltage regulators. The numerical method that permit to solve the oscillation equations it is from a multi-machine system named fourth order Runge-Kutta, getting an appraisal of the angular behavior from the synchronous machines with about to the time.